Contemporary career from the perspective of anindividual : career models, their interrelationships and implications - Renata Korsakienė; Rasa Smaliukienė (Business: Theory and Practice, 2014)
Changes in economic, social and technological environment have resulted in unpredictability of jobs and shifted the interest of scholars from the traditional career to new career models. On the other hand, contemporary scientific literature focused on protean and boundaryless career lacks empirical evidence and support. The presented paper aims to discuss the interrelationships and implications of new career models. The comprehensive analysis of scientific literature has led to the conclusion, that contemporary career models are seen as complementary to each other and the role of organisations remains significant in career management of individuals. The research of the authors contributes to other findings and implies that balanced approach toward career development should be adopted.